Patient-Reported Outcomes of Femoral Head Fractures with a Minimum 10-Year Follow-Up. Issue 12 (December 2020) - Koerner, Michael; Westberg, Jerald; Martin, Jill; Templeman, David
Abstract : Objective: To evaluate the clinical-reported and patient-reported outcomes of patients with femoral head fractures treated at a single level I trauma center with a minimum 10-year follow-up. Design: Retrospective review. Setting: Academic Level-1 Trauma Center. Patients/Participants: One hundred one consecutive femoral head fractures were identified for this study. The final study group consisted of 28 patients with a minimum of 10 years of clinical follow-up. Intervention: All patients were treated with one or in combination with the following treatments: nonoperative management, open reduction and internal fixation, fragment excision, or total hip arthroplasty (THA). Main Outcome Measures: The Oxford Hip Score (OHS) at final follow-up along with clinical and radiological complications: infection, avascular necrosis, post-traumatic osteoarthritis, heterotopic ossification, and conversion to THA. Results: Twenty-eight patients with greater than 10 years of follow-up were included in this evaluation. The average follow-up was 14 years, and the average age was 39.2 years. Surgical management occurred in 86% of patients, and the mean time to definitive treatment was 3.7 days. Overall, 21 patients (75%) experienced a complication. Seven patients (30%) were later converted to a THA at an average of 6.4 years from initial injury. Three of the 7 late THA conversions (43%) required later revision. OHSs were obtained in all 28 patients at the final follow-up. The average OHS was 36.6. The mean OHS of the native hips was 37 at an average follow-up of 13.6 years. The mean OHS of primary THA was 41, and the mean OHS of secondary THA at final follow-up was 31.4, but this was not statistically significant ( P = 0.134). Conclusions: Patients should be counseled that the long-term results of open reduction and internal fixation may be satisfactory but unfortunately are not predictable. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.